(untitled) (Research, Society and Development, 2025)
Antimicrobial Resistance (AMR), particularly in ESKAPE pathogens, is a critical global public health threat. These multidrug-resistant pathogens form biofilms, creating an urgent gap with pharmaceutical innovation. Objective: This bibliometric analysis aims to map the conceptual structure and the emerging trends within this scientific field. Methodology: A descriptive, retrospective bibliometric analysis (2015-2025) was conducted on scientific output indexed in the Scopus database. Performance metrics (Lotka’s and Bradford’s Laws) and scientific mapping were applied. Data processing in R with Bibliometrix was used to analyze keyword co-occurrence networks, international collaboration, and thematic classification. Results: Scientific production shows sustained growth, concentrated in core journals. There is marked geographical inequality, with the highest output from high-income countries. The co-occurrence network confirms solid thematic clusters centered on AMR mechanisms, biofilm formation, and virulence. Discussion: Findings confirm thematic concentration on microbiological fundamentals and the shift toward alternative therapies such as phage therapy and drug repurposing. The centralization of output in high-impact nodes reveals a significant gap in knowledge circulation. Conclusion: The study confirms AMR as a global priority and an expanding field. Transnational collaboration is critical for progress. The main implication is the need to strengthen multicentric research in vulnerable contexts to achieve a comprehensive understanding and ensure the global applicability of therapeutic strategies against ESKAPE.